ANALISIS TINGKAT PENGGUNAAN MEDIA SOSIAL DALAM PEMASARAN UNTUK MENINGKATKAN KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE - ANDROID - Kasmari .; Mochammad Irsad (Jurnal Ilmiah Dinamika Teknik, 2017)
Research using Importance Performance Analysis (IPA). Where is the concept of a multi-attribute models. This technique identifies strengths and weaknesses of the use of social media in marketing by using two criteria: social media attributes and student purchasing decisions. The aim of research to determine the level of use of social media for students to purchase keutusan android smartphone users at the Faculty of Economics and Business of University Stikusbank Semarang. To determine the attributes that prioritized social media to be repaired and maintained. analyzed the level of suitability and Cartesian diagrams. Concordance rate is used to determine the level of use of social media popularity gap between the perception or performance and expectations of students, the dimensions of which are used among others Means of Communication (X1) 0.88, Responsiveness Media promotion (X2) 0.90, Means Research (X3) 0.88, More known (X4) 0.91. Cartesian diagram is used to determine the attributes that prioritized social media to be repaired and maintained. The analysis of gaps (gap) of a Communication Facility dimension (X1), Responsiveness Media promotion (X2), Research Facilities (X3), more known (X4). The results of the analysis of Cartesian diagram attributes are a top priority for repair (quadrant), namely items 3, 4, 20, 24 (quadrant II), namely 13, 17, 18, 21, 22 (kudran III) ie items 1, 5, 6, 10, 11 (quadrant IV) are items 2, 7, 9, 12, 14, 15,16, 19. Keywords : Care, Hope, Social Media in Pemasaan, Cartesian diagram, Level Purchasing Decision.